Electrochemical Studies on Acrylonitrile Grafted Polystyrene and Carbon Nanomaterials as Modified Electrodes - Radhi, Muhammed Mizher (2010)
Acrylonitrile was successfully grafted on polystyrene using gamma-irradiation technique. The new grafted polymer (GP) was characterized and its properties were investigated. In this study, it is found that 2 gm of polystyrene, 90% (w/w) acrylonitrile monomer, 2% (w/w) ferrous ammonium sulfate (FAS) catalyst and 1.25 Mrad gamma dose are the optimized conditions required for the polymerization of GP. The grafted polymer was proved by Fourier transform infrared (FTIR), thermogravimetry analysis (TGA) and viscosity techniques. A mechanism is presented to explain the formation of GP. A grafted polymer electrode (GPE) and a grafted polymer reference electrode (GPRE) were fabricated as a working and reference electrode respectively and used in electroanalysis. These new GPE and GPRE were evaluated using K3[Fe(CN)6] in 0.1 M KCl as standard solution during cyclic voltammetry. The redox waves of Fe(III)/Fe(II) couple match well with those reported. Both the new GPE and GPRE show good hardness, insolubility, reliability and stability at high temperature and at different pH. A glassy carbon electrode (GCE) was modified to mediate a GP by using a solution evaporation method to produce a new modified electrode, GP/GCE. The redox process of K3[Fe(CN)6] during cyclic voltammetry was studied using the GP/GCE. It was found that the peak separation (ΔEpa,c) between the redox peaks of ferricyanide ion in aqueous solution is 82 mV and the current ratio of redox peaks, (Ipa/Ipc) is 1 for the GP/GCE, indicating that good reversibility with good conductivity of the modified electrode. Hence, it can be used for voltammetric analysis. The modified electrode GP/GCE shows good hardness, high adhesion to metal surfaces of electrode collectors, insolubility and stability at high temperatures and at different pH levels. In addition, the sensitivity of the electrode under the cyclic voltammetry is significantly dependent on pH, the electrolyte used, temperature and the scan rate. Based on the surface charge determined by chronocoulometry (CC), GP/GCE appears more conductive than GCE. The diffusion coefficient of 7.2x10-7 cm2 s-1 for the ferricyanide ion in the redox process was determined using a chronoamperometry (CA). The modified glassy carbon electrodes (GCE) by microcrystals of fullerene C60 (C60/GCE), activated carbon (AC/GCE) and carbon nanotubes (CNT/GCE) have been studied extensively mediating some selected heavy metal compounds such as Mn2+, Hg2+ and Cd2+ in aqueous electrolyte. GCE was modified with carbon nanotubes CNT, AC, and C60 with and without Li+ dopant by mechanical attachment and solution evaporation methods. These new modified working electrodes abbreviated as CNT/Li+/GCE, AC/Li+/GCE and C60 /Li+/GCE were used in the presence of aqueous KCl electrolytes. Under conditions of cyclic voltammetry, the potential for oxidation and reduction peaks of the heavy metal ions such as Mn2+, Hg2+ and Cd2+ were shifted to lower potential (toward the origin) and the current was enhanced significantly relative to the modified electrodes. The sensitivity of the electrodes under the cyclic voltammetry was significantly dependent on different pH, temperature, scan rate and concentration. Positive interference with other heavy metal ions, such as Ca2+, Cu2+, Ni2+ were observed as the presence of these interfering metal ions causes further increase in the redox peaks of the heavy metal ions of interest. Based on the surface charge determined by chronocoulometry (CC), the modified electrodes appear to be more conductive when the heavy metal ions were used in comparison with the bare GCE. Diffusion Coefficient (D) for the heavy metal ions was determined using chronoamperometry (CA). Excellent analytical recovery results of the heavy metal ions in blood sample and seawater were observed at the above mentioned modified GCE.